(untitled) (Alternautas, 2022)
The work of Nestor Garcia Canclini was, and still is, an important source of inspiration and learning for research in Latin America. In this article by Daniel Mato and translated by Emilie Dupuits, the author comments on some key aspects of his work that are of particular importance and usefulness for contemporary social research. The title of this post tries to name synthetically some of these aspects, or, more accurately, his interpretation of them.